Eksplorasi Keterkaitan antara Citra Destinasi, Personalitas Destinasi dan Niat Berkunjung Kembali ke Destinasi Wisata - Heri Setiawan; Jusmawi Bustan; Abd. Hamid; Ummasyroh Ummasyroh (Politeknik Negeri Bengkalis, 2019)
Most countries try to develop tourism destinations with a variety of strategies to be able to compete with other destinations. This study is designed to explore the relationship between destination image, destination personality, and intention to re-visit tourists to tourism destinations. The approach used in this study is a quantitative approach to the design of causality research. The research sample is domestic tourists who have visited tourist destinations in Palembang such as Benteng Kuto Besak, Jaka Baring Sport City, Kemaro Island, Kambang Iwak Park, Punti Kayu Park, Siguntang Park, Taman Purbakala Sriwijaya totaling 192 respondents. The structural equation model is used to test the model developed using the maximum likelihood (ML) estimation method using AMOS 22.0. The results of the study explained that there is a linear relationship between destination images and destination personalities. There is no linear relationship between the destination images with the intention to visiting again. Then, there is a linear relationship between personalities of the destination with the intention of visiting again.